Quantifying erosion and retention of silicon carbide due to D plasma irradiation in a high-flux linear plasma device. (March 2021) - Sinclair, G.; Abrams, T.; Bringuier, S.; Thomas, D.M.; Holland, L.; Gonderman, S.; Yu, J.H.; Doerner, R.P.
Highlights: Erosion and retention properties of SiC were studied via D plasma exposures. Chemical sputtering of carbon from SiC was 4× lower, on average, than from graphite. Si chemical erosion was not measured from SiC, supporting previous findings. D trapped in SiC was desorbed via one major signal around 1000 K. Total D retention was within a factor of 2 between SiC and W at conditions tested. Abstract: Silicon carbide (SiC) may be a viable option for future plasma-facing components (PFCs) due to its low hydrogenic diffusivity, high temperature strength, and mechanical resilience to neutron damage (Causey et al., 1978). The erosion and retention properties of SiC were quantified via deuterium plasma exposures in the PISCES-E RF plasma source on SiC-coated graphite samples at impact energies between 20 eV and 90 eV, surface temperatures of 500 K and 950 K, and fluences between 0.4 and 1.0 × 10 24 m −2 . The chemical sputtering yield of carbon from SiC was estimated by optical spectroscopy, varying between 0.0012 and 0.0083 depending on the deuterium impact energy. Chemical sputtering yields from graphite were 4× higher, on average, than yields from SiC and were largely consistent with previous analytic formulations. Chemical erosion of silicon atoms from SiC was not detected from the SiD molecular band, but the lack of Si surface enrichment at low Ei suggests that a non-collisional Si erosion source may be present. The retention of implanted deuterium in SiC was 2× higher than that in tungsten at 500 K. Most D retained in SiC was desorbed at a peak temperature 1000 K, and the desorption rate only varied slightly with impact energy and surface temperature. Fundamental differences in desorption behavior between Si, graphite, and SiC samples suggested that the SiC cubic lattice possessed unique trapping sites that cannot solely be attributed to Si-D or C-D bonds. New questions regarding preferential erosion and uncharacterized defects motivate expanded testing in linear and toroidal devices.